A new species of Diadema (Echinodermata: Echinoidea: Diadematidae) from the eastern Atlantic Ocean and a neotype designation of Diadema antillarum (Philippi, 1845) - Rodríguez, Adriana; Hernández, José Carlos; Clemente, Sabrina; Coppard, Simon Edward (Zootaxa, 2013)
Diadema africanum sp. nov. Rodríguez et al. 2013 occurs in the eastern Atlantic Ocean at depths of 1–80 meters off Ma-deira Islands, Salvage Islands, Canary Islands, Cape Verde Islands, Sâo Tome Islands and at the continental coast off Sen-egal and Ghana. This species was previously considered an eastern Atlantic population of D. antillarum. Genetic distances between the holotype of D. africanum and the neotype of D. antillarum herein designated, measured 3.34% in Cytochrome oxidase I, 3.80% in ATPase-8 and 2.31% in ATPase-6. Such divergence is similar to that already highlighted between other accepted species of Diadema. Morphometric analysis of test, spine and pedicellarial characters also separated D. africa-num from D. antillarum and reveals that this new species is morphologically similar to D. antillarum ascensionis from the mid Atlantic. The tridentate pedicellariae, which have been shown to have diagnostic characters which discriminate among species of Diadema, occur as both broad and narrow valved forms in D. antillarum from the western Atlantic. In D. africanum the tridentate pedicellariae occur only as a single form which is characterized by moderately broad and curved valves, with an expanded distal gripping region. This form of tridentate pedicellaria is very similar to that of D. antillarum ascensionis from the central Atlantic, with only slight variations in valve serration and valve curvature differ-entiating the two forms.